Mapping research on the social impact of the arts: what characterises the field? [version 2; peer review: 2 approved] - Cia Gustrén; Sofia Lindström Sol; Johan Eklund; Gustaf Nelhans; Roger Blomgren; Jenny Johannisson (Open Research Europe, 2022)
This article explores the broad and undefined research field of the social impact of the arts. The effects of art and culture are often used as justification for public funding, but the research on these interventions and their effects is unclear. Using a co-word analysis of over 10,000 articles published between 1990 and 2020, we examined the characteristics of the field as we have operationalised it through our searches. We found that since 2015 this research field has expanded and consists of different epistemologies and methodologies, summarised in largely overlapping subfields belonging to the social sciences, humanities, arts education, and arts and health/therapy. In formal or informal learning settings, studies of theatre/drama as an intervention to enhance skills, well-being, or knowledge among children are most common in our corpus. A study of the research front through the bibliographic coupling of the most cited articles in the corpus confirmed the co-word analysis and revealed new themes that together form the ground for insight into research on the social impact of the arts. This article can therefore inform discussions on the social value of culture and the arts.